Cutaneous and systemic lymphomas of concordant or discordant B- and T-cell phenotype in the same patient: two case reports. (October 2021) - Martins, Ana Silva; Sanches, Maria; Alves, Daniela; Polo, Blanca; Moreno, Raul; Ferreira, Cristina; Almeida, Luis Soares; Raposo, João
Abstract : Background: The development of two different non-Hodgkin lymphomas in the same patient is an unlikely coincidence due to the low prevalence of each malignancy. However, a significantly increased risk of developing a second lymphoma was observed in patients with cutaneous T-cell lymphoma (CTCL) in both population-based and clinic-based data [1 ]. Most cases reported describe the occurrence of concomitant lymphomas of discordant B- and T-cell phenotypes, mainly MF and chronic lymphocytic leukemia [2 ]. On the opposite, few cases of concomitant systemic and cutaneous B-cell lymphomas have been reported [3, 4 ]. Case 1: A young woman with the diagnosis of three B-cell lymphomas. At 37 years-old, primary cutaneous marginal zone lymphoma (pcMZL) was diagnosed on a right cervical cutaneous nodule and relapsed 3 years later on the temporal region; both lesions were excised. One year later, diffuse large B-cell lymphoma (DLBCL) diagnosis was made on an isolated cervical right lymphadenopathy. She was staged as Ann Arbor stage I and treated with CHOP (cyclophosphamide, doxorubicin, vincristine and prednisolone) regimen for 6 cycles with complete response (CR). Two years later, the diagnosis of follicular lymphoma was made on a lymph node biopsy. The patient remained with asymptomatic cervical and inguinal lymph node enlargement for 10 years until extra-nodal involvement ensued. At that time, treatment with R-FC (rituximab-fludarabine and cyclophosphamide) followed by radiotherapy achieved partial response (PR). In the following 3 years, follicular lymphoma progressed twice and was retreated with radiotherapy with PR. After 5 years of follow-up, the patient remains asymptomatic without further treatment. Case 2: A patient with two lymphomas of discordant phenotype. The 51 years-old Caucasian man presented at our dermatology clinic with a 10-years history of cutaneous erythematous patches and plaques on the abdomen and upper limbs. The 3 cutaneous biopsies made were consistent with the diagnosis of mycosis fungoides and workup excluded systemic involvement. As such, a diagnosis of mycosis fungoides (MF) stage IB was made. The patient had been observed on another hospital facility 3 months before, when he presented bilateral inguinal lymph node enlargement. The excisional biopsy revealed follicular lymphoma but the pathology examination review of the sample at our hospital diagnosed DLBCL, non-germinal center type, that was staged as Ann Arbor II. He started chemoimmunotherapy with R-CHOP regimen for 6 cycles, leading to CR and a mild improvement on MF (downstaging to IB). The patient is currently on topical steroids for MF and DLBC lymphoma is still on remission after 1 year of follow-up. Conclusions: The occurrence of concomitant systemic and cutaneous lymphomas of discordant or concordant lineages may represent a diagnostic challenge. As the treatment of each lymphoma is often different, their correct identification is critical for optimal management of both diseases.